Representation in a context across political orders and the Chinese case. Issue 4 (2nd October 2019) - Heberer, Thomas
Abstract: This paper sheds light on the issue of political representation in an authoritarian context, taking China as a case study. In the academic literature, the concept of political representation is primarily related to mechanisms of representation in a democratic setting, used in a rather technical or normative sense and concerned with institutionalized representation in legislatures and parliaments, with a strong focus on elections by which citizens express their political will. The conviction prevails that only persons elected in a competitive electoral procedure can be conceived as legitimate representatives. Widely lacking in the scholarly literature are approaches which explain the nature of political representation in a non-democratic setting. To date, patterns of formal and informal representation in an authoritarian context constitute a 'black hole' in the literature on representation. This article tries to answer two research questions: (1) How does representation in an authoritarian system work? (2) What can we conclude from the Chinese case with regard to representation in an authoritarian setting? The article first conceptualizes representation in an authoritarian setting. Second, it examines which mechanisms of representation and representative claims exist in China. Third, it distinguishes between five mechanisms of political representation: formal, informal, symbolic, traditional and digital. It is argued that informal patterns of representation are crucial since formal ones are more strictly controlled. A new and specific role is played by 'digital representation': a vigorous form of representation via the cyberspace, spawning new and innovative modes of formal, informal and symbolic political representation. In the conclusions, the author considers what his findings regarding the Chinese case mean for the concept of representation in authoritarian states. He also explains why representation in an autocratic context can produce political output and exhibit legitimacy among the represented.